First results of multicortical screw anchoring compared with conventional bicortical screw placement in the sacrum: A biomechanical investigation of a new screw design. (May 2019) - Grevenstein, David; Meyer, Carolin; Wegmann, Kilian; Hackl, Michael; Bredow, Jan; Eysel, Peer; Prescher, Andreas; Scheyerer, Max J.
Abstract: Background: Bicortical screw fixation is an established technique to increase screw strength in vertebral bodies, although it is associated with several complications, for example screw-loosening. Cement augmentation can increase stability of screw-fixation but can also cause various complications, such as cement-leakage or cement embolism. In this study, we tested a new, multicortical screw fixation technique in the sacrum. Methods: Four fresh-frozen sacrums were used. In group 1, standard screw insertion, with sagittal parallel and axial convergent screw-drive was performed. In group 2, the screw-drive of the first screw was similar to the screw-drive in group 1. In addition, a second screw was inserted descending into the intended hole in the head of the screw and at a stable angle. Therefore, the screws of the multiloc humerus nail-system (Synthes) were used. The specimens were connected to a testing-machine and underwent cyclic axial loading with an increase in the load after each completed stage. Findings: Multicortical screw fixation leads to a significant increase in the number of completed cycles and a significantly increased load until failure. Interpretation: Multicortical screw fixation in the sacrum offers a stronger attachment of the screws. In the future, multicortical implants, which fulfil the criteria demanded in spine surgery, can offer higher stability and may decrease the loosening rates of the implanted screws. Highlights: Sacral bicortical screw fixation is commonly used for strength and stability. This study tested a new, multicortical screw fixation technique. Fresh-frozen sacrums were used to compare bicortical and multicortical techniques. Multicortical screw fixation resulted in more strength, stability and load bearing.